2021
DOI: 10.1016/j.hpb.2021.04.027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative chemotherapy and chemoradiotherapy on pancreatic fistula and other surgical complications after pancreatic resection: a systematic review and meta-analysis of comparative studies

Abstract: The effect of preoperative chemotherapy and chemoradiotherapy on pancreatic fistula and other surgical complications after pancreatic resection: a systematic review and meta-analysis of comparative studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Neoadjuvant therapy could impact the texture of pancreatic tissue, which has been associated with reduced rates of POPF. 32 The results of the present study should be interpreted considering several limitations. First, there was potential information bias regarding the lack of information on patient's preoperative nutritional status as no data on nutritional status are available in the nationwide, prospectively recorded DPCA.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Neoadjuvant therapy could impact the texture of pancreatic tissue, which has been associated with reduced rates of POPF. 32 The results of the present study should be interpreted considering several limitations. First, there was potential information bias regarding the lack of information on patient's preoperative nutritional status as no data on nutritional status are available in the nationwide, prospectively recorded DPCA.…”
Section: Discussionmentioning
confidence: 87%
“…Neoadjuvant therapy could impact the texture of pancreatic tissue, which has been associated with reduced rates of POPF. 32 …”
Section: Discussionmentioning
confidence: 99%
“…An interesting and less radical concept in high-risk patients is one-time preoperative radiotherapy, aiming to obtain local fibrosis in the pancreatic neck where the future pancreatico-enterostomosis will be created (FIBROPANC study) [ 44 ]. Hence, pancreatic cancer patients who are treated with chemo(radio)therapy have a lower chance to develop clinically relevant POPF, with radiotherapy as independent predictor [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one randomized phase II trial has been presented that directly compared neoadjuvant multiagent chemotherapy with or without RT. 23,24 The ALLIANCE A021501 trial compared neoadjuvant mFOLFIRINOX (8 cycles) versus mFOLFIRINOX (7 cycles) followed by SBRT (33)(34)(35)(36)(37)(38)(39)(40) Gy in 5 fractions) or hypofractionated image-guided RT (25 Gy in 5 fractions). After inclusion of 56 patients, the RT arm was closed due to futility regarding the R0 resection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies, however, have found no difference in postoperative complications between patients with and without preoperative Moreover, the rate of postoperative pancreatic fistula was lower in patients who received preoperative RT. 37,38 Currently, 3 randomized trials are assessing the role of neoadjuvant RT for BR PDAC. The 3-arm BRPCNCC-1 trial is comparing neoadjuvant gemcitabine plus nab-paclitaxel with or without SBRT with S1 plus nab-paclitaxel with SBRT in 150 patients.…”
Section: Discussionmentioning
confidence: 99%